2003
DOI: 10.1029/2003jb002411
|View full text |Cite
|
Sign up to set email alerts
|

Slope failure and volcanic spreading along the submarine south flank of Kilauea volcano, Hawaii

Abstract: [1] New multichannel reflection data and high-resolution bathymetry over the submarine slopes of Kilauea volcano provide evidence for current and prior landsliding, suggesting a dynamic interplay among slope failure, regrowth, and volcanic spreading. Disrupted strata along the upper reaches of Kilauea's flank denote a coherent slump, correlated with the active Hilina slump. The slump comprises mostly slope sediments, underlain by a detachment 3-5 km deep. Extension and subsidence along the upper flank is compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 54 publications
4
110
0
1
Order By: Relevance
“…The decompression generated by the normal faults to the northwest and by gravity collapse to the southeast probably influenced the concentration of the recent eruptive activity in these sectors; such features are observed in the Canaries islands and along the Kilaua volcano in Hawaii [1,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decompression generated by the normal faults to the northwest and by gravity collapse to the southeast probably influenced the concentration of the recent eruptive activity in these sectors; such features are observed in the Canaries islands and along the Kilaua volcano in Hawaii [1,19].…”
Section: Discussionmentioning
confidence: 99%
“…Un petit glissement est relevé à l'Ouest au Les glissements sous-marins sont des phénomènes destructifs qui affectent couramment les édifices volcaniques comme la chaîne hawaiienne [18], les Canaries [1], la Polynésie [6] ou La Réunion par exemple [15,21]. Plusieurs mécanismes sont invoqués à l'origine des glissements, dont les intrusions massives de dykes [11,14,19], les augmentations des valeurs de pentes en stade post-bouclier [25], les vibrations des séismes [23] [27] comme une ancienne caldeira aérienne d'axe N140°. À terre, cet appareil comporte principalement des laves basaltiques mio-pliocènes et des pitons de phonolites pliocènes [7].…”
Section: /24unclassified
“…Even so, the source areas for these landslides were often difficult to identify because subsequent lava flows and slope sediments filled in the scars [e.g., Lipman et al, 1988]. Additionally, lateral spreading and deformation of Hawaiian volcanoes throughout their evolution means that volcanic rift zones may evolve over time [Swanson et al, 1976;Dieterich, 1988;Denlinger and Okubo, 1995;Morgan et al, 2003]. Constraining the past configurations of volcanoes and their rift zones is the key to unraveling the growth history of the island [Fiske and Jackson, 1972;Holcomb et al, 2000], and also provides insight into the present-day deformation of the volcanoes, i.e., ongoing surface movements and earthquake activity [Denlinger and Okubo, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…At the Cordillera Dorsal an 8-9 km wide valley was formed, with an amphitheatre-shaped head, an area of 73 km 2 and prominent side walls. The origin of this Güimar Valley was interpreted by Navarro and Coello (1989) to be the result of landslide processes, the same origin as for the Orotava Valley (Figure 2). Geological studies of Güimar Valley showed that it was formed by a flank collapse younger than 0.83 Ma, the most recent age obtained for lava flows in the scarp (Ancochea et al, 1990).…”
Section: South Sectormentioning
confidence: 75%
“…Day et al (1999) described the well developed topographic San Andrés fault scarp on the flank of the steep-side NE rift of El Hierro, and related it to an aborted giant collapse; Vidal and Merle (2000) used a model to prove that the reactivation of a vertical fault in volcanic cones generates normal faults and an upturning of the layers that induces a flank collapse. In Hawaii, the Hilina slump has been recognized as an active landside that breaks the mobile southeast flank of Kilauea volcano and is headed on land by a system of seaward facing normal faults (Morgan et al, 2003). From the study of the characteristics of this scarp, its relation with the on-land features of Güimar Valley and the comparison with other avalanches in the Canaries, we suggest that a tectonic process seems to have created the scarp.…”
Section: South Sectormentioning
confidence: 83%